Dias de Ansiedad (triptych) [detail]. - Herrera, Marylu. (Tufts Archival Research Center, 2019)
Installation view from Liminal Space: 2019 SMFA Senior Thesis Exhibition. Thesis project statement: Color is not often perceived when we think about mental health. However, I think it is the best way to embrace and push the conversation into our everyday lives. While working in a non-profit mental health organization as a graphic artist, there was no push for color and composition.